Confirmatory factor analysis intellectual capital village apparatus on improving community services - Hamdani, Deky; Amri, Faisal; Sari, Ayu Esteka; Sudirman, Sudirman; Anugrah, Fadli (International Journal of Enterprise Modelling, 2025)
This study aims to analyze and confirm the intellectual factors of village apparatus capital in improving services to the community. The method used in this study is Confirmatory Factor Analysis (CFA), which aims to test the validity and reliability of the intellectual construct of capital consisting of human capital, structural capital, social capital, relational capital, cultural capital, customer capital, organizational capital, and service capital. Data was collected through a survey of village officials in Sungai Penuh City using a questionnaire that had been tested previously. The results of the measurement of CFA first order on the latent variable there is one variable that is not significant, namely service capital with an LFE value of < 0.5. Intellectual capital exerts a good and considerable influence on the performance of village apparatus in Sungai Penuh City, while knowledge has no positive and significant effect on the performance of village apparatus in Sungai Penuh City. To see the role of knowledge as an intervening variable, it can be concluded that the correlation between Intellectual capital and the performance of village apparatus in Sungai Penuh City is better without going through the knowledge variable as a mediating variable in improving the performance of the village apparatus in Sungai Penuh City.